The Genetic Aspects of Periodontitis Pathogenesis and the Regenerative Properties of Stem Cells - Klaudia Ustianowska; Łukasz Ustianowski; Estera Bakinowska; Kajetan Kiełbowski; Joanna Szostak; Martyna Murawka; Bartosz Szostak; Andrzej Pawlik (Cells, 2024)
Periodontitis (PD) is a prevalent and chronic inflammatory disease with a complex pathogenesis, and it is associated with the presence of specific pathogens, such as Porphyromonas gingivalis. Dysbiosis and dysregulated immune responses ultimately lead to chronic inflammation as well as tooth and alveolar bone loss. Multiple studies have demonstrated that genetic polymorphisms may increase the susceptibility to PD. Furthermore, gene expression is modulated by various epigenetic mechanisms, such as DNA methylation, histone modifications, or the activity of non-coding RNA. These processes can also be induced by PD-associated pathogens. In this review, we try to summarize the genetic processes that are implicated in the pathogenesis of PD. Furthermore, we discuss the use of these mechanisms in diagnosis and therapeutic purposes. Importantly, novel treatment methods that could promote tissue regeneration are greatly needed in PD. In this paper, we also demonstrate current evidence on the potential use of stem cells and extracellular vesicles to stimulate tissue regeneration and suppress inflammation. The understanding of the molecular mechanisms involved in the pathogenesis of PD, as well as the impact of PD-associated bacteria and stem cells in these processes, may enhance future research and ultimately improve long-term treatment outcomes.